AKTIVITAS AMILASE PENDEGRADASI PATI MENTAH DARI BAKTERI TANAH TEMPAT PEMBUANGAN AKHIR BUKIT PINANG - Putri, Amanda Aulia; Astuti, Winni; Pratiwi, Djihan Ryn (JURNAL ATOMIK, 2024)
Raw starch-degrading amylase (RSDA) is a hydrolytic enzyme that can degrade raw starch into glucose. This study was conducted to obtain raw starch-degrading amylase-producing bacteria from the soil of the Bukit Pinang Landfill, Samarinda City. Isolation of bacteria using the spread plate method. Screening of RSDA-producing bacteria using nutrient media to contain raw starch. Isolation of bacteria obtained 10 single colonies of bacteria. The isolated bacteria were selected for their ability to produce RSDA. All single colonies of bacteria could produce RSDA and their activity was tested quantitatively using the 3,5 Dinitrosalicylic Acid (DNS) method. Bacteria with the TPA 1 colony code had the highest activity of 3.837 U/mL.